2012
DOI: 10.4028/www.scientific.net/amr.476-478.227
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance of Water Soluble Salt-Resistant Polymers for Chemical Flooding

Abstract: The basic requirement of polymer for chemical flooding was introduced, development progress and performance evaluation of salt-resistant polymers for chemical flooding were discussed, and development direction of polymers for chemical flooding was indicated in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…A consideration of polymer microstructures for enhanced oil recovery may include the molecular architecture, the statistical distribution of comonomer units along a linear backbone, or both. The rheology of polymer solutions can change drastically, depending on whether linear or branched polyacrylamides are employed [24,25]. In fact, Zhu et al [25] reported that using nonlinear architectures (comb-shaped, branched, and star-shaped polymers) improved the salt tolerance in terms of viscosity modification and long-term stability.…”
Section: Polymer Microstructurementioning
confidence: 99%
See 4 more Smart Citations
“…A consideration of polymer microstructures for enhanced oil recovery may include the molecular architecture, the statistical distribution of comonomer units along a linear backbone, or both. The rheology of polymer solutions can change drastically, depending on whether linear or branched polyacrylamides are employed [24,25]. In fact, Zhu et al [25] reported that using nonlinear architectures (comb-shaped, branched, and star-shaped polymers) improved the salt tolerance in terms of viscosity modification and long-term stability.…”
Section: Polymer Microstructurementioning
confidence: 99%
“…The rheology of polymer solutions can change drastically, depending on whether linear or branched polyacrylamides are employed [24,25]. In fact, Zhu et al [25] reported that using nonlinear architectures (comb-shaped, branched, and star-shaped polymers) improved the salt tolerance in terms of viscosity modification and long-term stability. As described earlier (in Figure 2), linear polymer molecules can be significantly affected by charge effects in solutions; high salinity environments can cause polymer coils to shrink, thus reducing the hydrodynamic volume and lowering the viscosity modification ability.…”
Section: Polymer Microstructurementioning
confidence: 99%
See 3 more Smart Citations